Incorporating iron fortificant in ultrasonicated waxy rice led to its stickier and firmer characteristics - Bonto, Aldrin; Camacho, Drexel; Sreenivasulu, Nese (Maximum Academic Press, 2024)
Incorporating iron in milled rice is an excellent recommendation for regaining mineral loss during milling and addressing micronutrient deficiency issues. This paper investigated the waxy rice variety iron fortification on sonicated milled grains and the effects of iron on the textural attributes of cooked fortified rice measured by a texture profile analyzer (TPA). Through enhanced absorption, modified rice grain induced by ultrasonic treatment has successfully increased iron uptake by 13.2% compared to non-sonicated waxy rice, with excellent retention of 99.33% after washing and cooking. The textural hardness of fortified sonicated rice significantly decreased (p < 0.01) by 19%, attributed to the microporous formation after the ultrasonic treatment. The rice stickiness increased by 39.5% after ultrasonication, and iron fortification was associated with the enhancement of the leached amylopectin-iron network resulting in a stronger attraction between the fortified rice and the TPA probe. The improved network formation in fortified rice was confirmed in the increased elastic (G') and viscous (G") moduli during temperature ramp and frequency sweep experiments. The observed impacts of micronutrient fortificants on the textural and rheological attributes may be helpful in the development of rice and rice products with enhanced eating quality.